Comparing the Clinical Efficacy of Topical Application of Virgin Coconut Oil and 1% Clotrimazole Cream as an Adjuvant to Systemic Antifungal in Chronic Dermatophytoses: A Randomized Controlled Trial - Chawla, Aakriti; Rastogi, Madhur Kant; Gahalaut, Pratik; Dubey, Varsha; Mahajan, Vasvi; Deshmukh, Rahul (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Dermatophyte infections have become a common entity with a prevalence ranging from 36.6-78.4%. Majority of the patients are from low socioeconomic background who favour topical treatment. High treatment costs of antifungal medication and consequent poor compliance have given rise to the need of an effective and economical topical preparation. Objectives: To compare efficacy of topical 1% clotrimazole versus virgin coconut oil application as an adjuvant to systemic antifungals in dermatophytosis. Materials and Methods: A total of 100 patients presenting to the dermatology outpatient department and diagnosed with tinea infection clinically and by potassium hydroxide mount were taken up for the study. The patients were randomized into two groups with 50 patients in each group. One group received virgin coconut oil while the other group received 1% clotrimazole cream twice daily application as the topical preparation. Mycological cure was assessed by potassium hydroxide mount and clinical improvement was assessed objectively by severity score for itch, changes in clinical signs and symptoms and subjectively by Dermatology Life Quality Index questionnaire. Statistical analysis was analyzed using SPSS software version 17. Results: Virgin coconut oil and 1% Clotrimazole had equivocal response after 12 weeks of treatment with respect to potassium hydroxide mount positivity, itch severity, clinical improvement and changes in Dermatology Life Quality Index scores when used along with systemic antifungal. Conclusion: Virgin coconut oil can be easily used as a topical emollient and antifungal preparation along with systemic antifungals in the treatment of dermatophytosis.